2016
DOI: 10.5505/tbdhd.2016.63308
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Ischemic Stroke: Clinical Features and Evaluation of Short-and Long- Term Tirofiban Therapy

Abstract: OBJECTIVE: Progressive ischemic stroke is a disorder frequently seen in neurological intensive care unit and stroke units. The purpose of this retrospective study was to evaluate the clinical features of progressive ischemic stroke patients in neurological intensive care unit, the short-and long-term efficacy of tirofiban therapy, and the adverse events observed. METHODS: The study included patients with minor-moderate progressive ischemic stroke diagnosed in the period between January and December 2014. The N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…27 In a case series published in our country, IV tirofiban treatment was given to 28 patients with progressive ischemic stroke (10 patients with large artery atherosclerosis, 9 patients with cardioembolism, 9 patients with small vessel disease); It was determined that the greatest decrease in the NIHSS score was in the small vessel disease group. 28 In the study reported by Zhang et al, which included patients with worsening under DAPT treatment, the patients were divided into 3 groups and followed up with tirofiban, tirofiban + ozagrel and ozagrel treatments. Although a decrease was observed in NIHSS scores in all three groups, the most significant decrease was observed in the tirofiban + ozagrel group at the 24th hour, 1st week and 2nd week.…”
Section: Discussionmentioning
confidence: 99%
“…27 In a case series published in our country, IV tirofiban treatment was given to 28 patients with progressive ischemic stroke (10 patients with large artery atherosclerosis, 9 patients with cardioembolism, 9 patients with small vessel disease); It was determined that the greatest decrease in the NIHSS score was in the small vessel disease group. 28 In the study reported by Zhang et al, which included patients with worsening under DAPT treatment, the patients were divided into 3 groups and followed up with tirofiban, tirofiban + ozagrel and ozagrel treatments. Although a decrease was observed in NIHSS scores in all three groups, the most significant decrease was observed in the tirofiban + ozagrel group at the 24th hour, 1st week and 2nd week.…”
Section: Discussionmentioning
confidence: 99%